Efforts to Overcome Social Prejudice against Waqf Land Certification in Padang Pariaman Regency Viewed from Fiqh and Its Practice - Yusnita Eva (Journal of Asian Wisdom and Islamic Behavior, 2023)
This research to identify the root causes of people's reluctance to accept the government's declaration to certify land throughout Indonesia. The community's preconception has resulted in many uncertified waqf lands. According to data obtained from the head of the Padang Pariaman Regency's National Land Agency (BPN), only 6% of waqf lands in V Koto Timur, Padang Pariaman Regency, have been certified. Data collected between 2015 and 2020 showed there are approximately 156 prayer rooms (musalla) and 24 mosques that have not been certified. Furthermore, waqf land disputes are common in the region, including the withdrawal of waqf land by heirs and the creation of agricultural land on waqf lands whose management is neglected. Religious factors influence the reluctance to certify waqf land, particularly among the people of Padang Pariaman who still follow the Syattariyah order and have strong faith in the Nagari leaders, particularly the penghulu, who find it difficult to accept their waqf land for certification. The community stereotype holds that waqf lands can be taken over by the government if they are certified. Other factors contributing to the ignorance include the fact that the person who made the waqf or his heir no longer resides in the area